OPTIMIZATION OF YTTRIUM TRANSPORT FROM BANGKAÃâÃâS XENOTIME CONCENTRATE USING TUBULAR SUPPORTED LIQUID MEMBRANE (TSLM) - DINI NURAENI (NIM : 10509097) ; Pembimbing Dr. Aminudin Sulaeman, MS
Xenotime is one of the Rare Earth Elements (REEÃ‚Â’s) natural resource. This mineral is one of the side results of tin processing at PT. Timah, Bangka. Based on X-Ray Florescence (XRF) analysis, Yttrium is the highest element in Xenotime mineral, which is 21.17 %. This element has been frequently used as magnet core, laser, metallurgy and also high temperature superconductor Yttrium Barium Copper Oxide (YBCO). During this research, other Y(III) and REE(III) from destruction result of NaOH has been separated from non-REE ion using Tubular Supported Liquid Membrane (TSLM), carrier solution in form of tributyl phosphate and di-(2-ethylhexyl) phosphate acid (D2EHPA) has been used with 0.25 M : 0.75M composition. Afterwards, optimization of pH feed phase with pH variation of 2.7;3;3.2;3.5 and 3.7 has been conducted, continue with optimization of receiving acid with variation of HCl, H2SO4and HNO3as well as optimization of receiving acid concentrate with variation of 1 M;1.5 M;2 M and 2.5M. Measurement of REE concentration from optimization result has been conducted with UV-Vis Spectrophotometry on 528 nm wavelength, after previously complexed using alizarin sulphonate. Based on previous parameters, the most optimum REE transport can be acquire on feed phase pH solution of 3.2 with H2SO4 as receiving acid in 2 M concentration. In this condition, the amount of REE that succeeded to be transported from feed phase to receiving phase is 55.84 %. Afterwards, composition analysis is being conducted using Inductively Coupled Plasma Atomic Emission Spectroscopy (ICP-AES) which resulted in transported Yttrium from feed phase to receiving phase increased from 38% to 57%.